Cardiology is where my heart is. (2nd June 2021) - Barton, Carys
Abstract : Carys Barton, heart failure nurse consultant, Chair of the British Society for Heart Failure Nurse Forum and Lynda Blue award nominee, discusses her career to date, her role as a consultant nurse, and the importance of mentors, the multidisciplinary team and learning from patients in achieving your goals.